Novel Small Molecules with Anti-Inflammatory and Anti-Angiogenic Activity in a Mouse Model of Oxygen-Induced Retinopathy - Adam S. Dayoub; Eesha Acharya; Adnan Dibas; Harlan P. Jones; Suchismita Acharya (Cells, 2024)
Retinopathy of prematurity (ROP) has a dual-phase disease pathology; in phase 1, hyperoxia-induced vaso-obliteration occurs in the retinal vasculature due to increased oxidative stress (OS) and inflammation, followed by phase 2, where hypoxia increases the overproduction of growth factors, inducing retinal neovascularization. Toll-like receptor 2 and -4 (TLR2 and TLR4) overactivation, hyper-inflammation, macrophages, and neutrophil infiltration contribute to the developing ROP. AVR-121 and AVR-123 are novel classes of small-molecule dual inhibitors of TLR2/4 tested in a human leukemia monocytic cell line (THP-1) and cord-blood-derived mononuclear cells (CBMCs). Both compounds inhibited TLR2/4 signaling-related inflammatory cytokines in THP-1 cells and inhibited VEGF-induced neovascularization in human retinal endothelial cells (HRECs), which are hallmarks of ROP. In an oxygen-induced retinopathy (OIR) murine model, the intraperitoneal injection of AVR-123 in the hyperoxia phase (P7–P12) or a nanosuspension eyedrop of AVR-123 in the hypoxic phase (P12–P17) significantly reduced vaso-obliteration, angiogenesis, and inflammatory cytokine profiles while not inhibiting the necessary growth factor VEGF in the juvenile mouse eyes. The results are consistent with our hypothesis that targeting the dual TLR2/4 pathway will reduce inflammation, angiogenesis, and vaso-obliteration in vitro and in vivo and reduce cytotoxic immune cells. AVR-123 has the potential to be developed as a therapy for ROP.